SUSTAINABLE CORPORATE GOVERNANCE INDEX AND FIRMS' PERFORMANCE: A STUDY ON PUBLIC LISTED COMPANIES IN MALAYSIA - SALAMI, OLADIPUPO LUQMAN (2015)
The increasing cases offinancial crises and corporate scandals have stained corporate governance reputation and further implanted doubt in the minds of stakeholders about the effectiveness of the current governance structure. In spite of the significance of corporate governance, identifying governance practices that result in corporate profitability has been very challenging. Similarly, identifying a well-accepted index to benchmark good corporate governance practices is also amajor concern. The purpose ofthis study is to develop a sustainable corporate governance index and examine the relationship between the index components and firm's performance. This study further examines the relationship between the sustainable corporate governance index and firm performance.